Contracts of Selling and Buying in the Contracts for the International Sale of Goods (Cisg) as the Means of Harmonization of the Laws International Trading - Seff, Syaugi Mubarak (International Journal of Social and Local Economic Governance, 2015)
The means of law harmonization is a very popular topic discussed by law scholars and business practitioners. The means of law harmonization through the substantive rules of the law of international trading is regarded efficient to prevent conflicts among systems of law which are subscribed by each country. The main goal of law harmonization is to look for homogeneity from fundamental principles through all of systems of law available (which will be harmonized). CISG in arranging the contract is viewed from the principle of consensus so that the absence of the things will not affect the validity of the contract. CISG does not arrange the relationship of law between the validity of a covenant and its implications. The contract of selling and buying in CISG, instead of requiring an agreement between two sides, requires real actions. The things being sold and bought must be free of rights and demand of the third side, expect the buyer who agrees to receive the things and complies to the rights and demands.